HUBUNGAN ANTARA FAKTOR INTERNAL KELUARGA BURUH MIGRAN DENGAN PERTAMBAHAN ASSET RUMAH TANGGA - Lia Mutiara Setia; Rukmadi Warsito; Georgius Hartono (Agric, 2013)
The purpose of this study were to find out: push and pull factors of migrant workers working abroad, and the relationship between internal factors with increasing household assets. This research was conducted in the District Tuntang and Pabelan. Type of research is explanatory research, using two approaches namely quantitative and qualitative analysis approach. Sampling method using Step Cluster Sampling. The main data analyzed in this study were obtained from a study entitled “Indonesian Workers (TKI) Role and Influence People’s Economy In Rural Areas In Central Java Province (Seeking Pattern Development Investments) Year-2". For completeness of the data conducted depth interviews with 12 randomly selected respondents in the said two villages. The analysis tools are Spearman rank correlation test with two-way T test with 95 percent confidence level.The results showed that:Push factors of migrant workers working abroad include the economic problems facing families, lack of jobs, low wages, and low levels of education.Pull factors working abroad include: salaries abroad are higher than in the country, opening the opportunity for an English course, the environment and the means of life more enjoyable, heart virtue employer in the country where they’ve worked before.There were a relationship between age, education, and number of family members with increasing household assets.